SCIENTIFIC APPROACHES TO STUDY AND PREVENTION OF VIOLATIONS OF SOCIAL AND PSYCHOLOGICAL ADAPTATION OF MEDICAL WORKERS - A. D. Golmenko; V. A. Khaptanova; E. L. Vygovskyy (Acta Biomedica Scientifica, 2015)
We consider syndrome of burnout as a violation of social and psychological adaptation of a person. It is presented as a dynamic process consisting of a "voltage" phase - a satisfactory adaptation; a "resistance" phase - adaptation and a stable phase of the "exhaustion" - maladjustment. The cause of burnout is institutional weaknesses at work, conflicts or disagreements with colleagues, fatigue, etc. Most susceptible to burnout syndrome are the specialists who have the working experience of 0-5 years and 20-25 years, and women are 4 times more likely to have it. We need to plan the combination of psychological and medical measures in the result of the preventive measures. We can apply psycho correctional and psycho developing work in a case of the satisfactory and stable adaptation. Otherwise, this requires the greater medical activities. The application of psychological tests allows us to assess the level of human adaptation abilities with a high degree of reliability as soon as possible and without great financial cost.